1995
DOI: 10.1016/s0022-5347(01)67494-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonsecretory Sigmoid Cystoplasty: Experimental and Clinical Results

Abstract: We report the results of experimental and clinical studies in which a de-epithelialized segment of sigmoid colon was used to cover the bladder dome where the mucosa was exposed (auto-augmentation) to increase bladder capacity. Experimentally, the technique was performed in 10 healthy female mongrel dogs and the intestinal segments established continuity perfectly over the exposed bladder mucosa. Histology 30 and 60 days postoperatively showed transitional epithelium lining the intestinal segment at the site of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…When the procedure is performed laparoscopically, possible mucosal perforation 9,12,13,18,21,23,25 is more dicult to correct than in the open approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the procedure is performed laparoscopically, possible mucosal perforation 9,12,13,18,21,23,25 is more dicult to correct than in the open approach.…”
Section: Discussionmentioning
confidence: 99%
“…The surgery time is 1 ± 2 h and hospitalisation 2 ± 6 days, as is corroborated in the literature. 10 ± 12,20 Additional implantation of an arti®cial sphincter is problematic, 18,21 even more so when the peritoneum is compromised after extensive pelvic surgery 10 and/or radiation. Over¯ow incontinence, acting as a`safety valve', is eliminated and thus bladder rupture may occur sooner.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported positive results with autoaugmentation, and the success was attributed to maintaining the bladder partially distended in the postoperative period. 4,5 With these observations as a basis, a silicone balloon was developed to be inserted into the bladder with the purpose of maintaining the diverticulum distended and thus avoiding cicatricial shrinkage. Studies using intravesical silicone balloons after autoaugmentation showed an increase of 329% in bladder capacity and a sevenfold increase in compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Demucosalized enteric segments combined with autoaugmentation offer an augmentation alternative with native bladder mucosa backed by a distensible muscular layer to provide strength and prevent scarring and contraction of the urothelial diverticulum. Experimental success with autoaugmentation colocystoplasty and autoaugmentation gastrocystoplasty (AAGC) led to the clinical use of these methods in children in the last decade [9][10][11][12][13][14]. However, in several clinical series AAGC has failed to produce a reliable augmentation effect [15][16][17].…”
Section: Introductionmentioning
confidence: 99%